Assessment of Tooth Shade Measurement Precision and Consistency with Digital Photography Calibration System - Barbara Delija Omazić; Dino Buković; Maja Žagar; Martina Šlaj; Davor Illeš (University of Zagreb. School of Dental Medicine, 2024)
Objectives: To ascertain the degree of precision and repeatability inherent in the "capture to edit" digital imaging system, namely the ColorChecker Passport Photo (X-Rite, MI, USA), and to juxtapose its performance against spectrophotometric assessments utilizing the Vita Easyshade® (Vita Zahnfabrik, H Rauter GmbH & Co. KG., Bad Sackingen, Germany) for the same set of teeth. Materials and methods: Eighty participants aged 19-25 were included in the study; all of them were Croatian students at the School of Dental Medicine, University of Zagreb. Color measurements of the maxillary right central incisors were performed in controlled, standardized laboratory conditions. The measurements were performed on calibrated digital photographs by an experienced clinician three times in a row, and L, a, and b of CIELAB color space values were recorded. The same procedure was performed using the Vita Easyshade 5.0 spectrophotometer (Vita Zahnfabrik, Bad Säckingen, Germany) in "Tooth single" mode. Results: The Cronbach's alpha was used as a repeatability measurement, thus revealing high consistency for both methods (α=0.94-1). Correlations were moderate (Pearson r=0.44-0.66 p<0.05). Testing confirmed that digital photography is inaccurate as spectrophotometry (p<0.05). An analysis of errors of means and their standard deviations revealed consistent discrepancies with minor deviations. Conclusion: The "capture to edit" method showed high consistency (Cronbach's α=0.94-0.96), and it exhibits comparability in terms of variability, reliability, and repeatability when compared to spectrophotometric measurement (VitaShade 5, VitaZahnfabrik). Disparities between the methods are evident and anticipated, yet they do not follow a consistently linear pattern. The combination of repeatability and consistency renders the "capture to edit" method a valuable tool for enhanced color mapping, thus facilitating comparisons between digital images.